UPAYA MEMINIMALKAN NON VALUE ADDED ACTIVITIES PRODUK MEBEL DENGAN PENERAPAN METODE LEAN MANUFACTURING - Misbah, Achmad; Pratikto, Pratikto; Widhiyanuriyawan, Denny (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2015)
Abstract The development of the furniture industry today is getting tougher so that businesses are required to make improvement and increase its performance thus able to grow and compete, one of them is CV. KOKOH is a company that manufactures, study chair covers, windows sills, doors, cabinets, tables, etc., by applying the make to order system. The focus of this research study on the seat due to dominate demand for these products amounted to 60% of all types of products manufactured. The purpose of this study is to identify waste and to analyze the causes of waste that occurs in the production process chair learning approach by using the tools of lean manufacturing value stream mapping (VSM), value stream analysis tools (VALSAT) and failure mode and affects analysis (FMEA). The result is that based process mapping activity, which belong to the value adding activity Is operating with a requirement for 6.840 second or as many as 45 activity or by 58,34%, necessary but non-value added activity is the activity of transportation and inspection needs 2.505 seconds or as much as 23 activity or by 21,37% as well as belonging to the non value adding activity is the activity of storageÂ and delay with the time requirements of 2.380 Seconds or as much as 34 activity or by 20,29% of the total time and decrease production time of 138,4 minutes into 11723,93 seconds occur time reduction of production lead time process for 9347 seconds whit a decrease in the amount of 79.72%.